THE EFFECT OF SERVICE QUALITY, CUSTOMER SATISFACTION, AND PERCEIVED VALUE ON CUSTOMER LOYALTY WITH COMMUNICATION QUALITY AS A MODERATING VARIABLE (A CASE STUDY OF BANK JATIM KCP MALANG CUSTOMERS) - Jefry Wahyu Santoso; Arief Noviarakhman Zagladi (CV. Radja Publika, 2026)
This study aims to analyze the influence of service quality, customer satisfaction, and perceived value on consumer loyalty, with communication quality as a moderating variable. A case study was conducted with customers of Bank Jatim KCP Malang to gain a deeper understanding of the factors driving loyalty in the context of regional banking. Data were collected through a survey method using questionnaires filled out by 100 respondents. Data analysis was carried out using quantitative methods with Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed hypotheses. The results show that service quality, customer satisfaction, and perceived value have a positive and significant effect on consumer loyalty. Additionally, communication quality has been proven to strengthen the relationship between these three independent variables and consumer loyalty. These findings support key theories such as SERVQUAL, the loyalty model, and Commitment-Trust Theory, enriching the related literature by confirming the role of communication quality in enhancing customer loyalty. This study emphasizes the importance for Bank Jatim and other regional banks to improve service quality, satisfaction, and perceived value, as well as to implement effective communication strategies to retain customer loyalty.